IMPLEMENTATION OF INFORMATION TECHNOLOGY GOVERNANCE BASED ON COBIT 4.1 IN THE CLASS I IMMIGRATION OFFICE OF TPI SEMARANG - M. Daiva Mahdyatha Wisaputra (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
Information systems will help companies integrate data, speed up and forecast data processing, improve information quality. Information technology management has many tools, one of which is Control Objectives for Information and Related Technology (COBIT) Control in COBIT is defined as a policy of procedures, practices and organizational structures designed to provide acceptable assurance that organizational goals will be achieved and events that do not expected to be anticipated.